2009
DOI: 10.21608/eajbsf.2009.17549
|View full text |Cite
|
Sign up to set email alerts
|

Changes in detoxifying enzymes and carbohydrate metabolism associated with spinetoram in two field-collected strains of Spodoptera littoralis (Biosd.)

Abstract: This study was conducted to investigate the biochemical defensive mechanisms in larvae of S. littoralis (Biosd.) (Lepidoptera: Noctuidae) collected from cotton fields in two Egyptian Governorates (Kalyobia and Behira), sprayed with spinetoram as well as its impact effect upon carbohydrate metabolism. The role played of spinetoram on different major defensive enzymes like glutathione S-transferases (GSTs) , non specific esterases and acetylcholinesterase(AChE) was discussed. It seems that these enzymes are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…The three tested insecticides caused a high significant reduction in both α and βesterase except pyridalyl which caused a significant increase in β-esterase. These results were in harmony with those recorded by Fahmy and Dahi (2009). The same reduction were obtained by Bakr et al, (2010).…”
Section: B-β -Esterasessupporting
confidence: 92%
“…The three tested insecticides caused a high significant reduction in both α and βesterase except pyridalyl which caused a significant increase in β-esterase. These results were in harmony with those recorded by Fahmy and Dahi (2009). The same reduction were obtained by Bakr et al, (2010).…”
Section: B-β -Esterasessupporting
confidence: 92%
“…Trehalse could be used as parameter for assessing the availability of nutrients (Ishaaya and Swirkski, 1976) in this study the activity of trehalase after 2 days from inoculation in all treatments except abamectin and mixture from M. anisoplaiae and plant extract from S. molle and in all treatments after 4 days is lower than control, this decrease due to The decreasing in trehalase activity may be due to toxicity stress of the treatments as indicating by many authors (Fahmy and Dahi, 2009, Elbanna et al, 2013and (Rashwan, 2013. Increase in activity of trehalase after 2 days from inoculation in abamectin are in parallel to (Dahi, et al, 2009) which found increase in activity of trehalase when treated Egyptian cotton leaf worm Spodoptera littoralis with avermectin While the activity is increased after 6 days from infection in case Neem, plant extract from S. molle and L-glutamic acid this result are in parallel to (Mohamed, 2014) which treated S. gregaria with Neem and found the activity of trehalase in insect which treated with Neem are higher than control. While in case of insect which treated with abamectin after 6 days the activity of trehalase is lower than control this result are in parallel to (Abo El-Ghar et al 1995) which found that when feeding Spodoptera littoralis larvae 5 ppm abamectin caused remarkable decrease in trehalase activities.…”
Section: Trhalasesupporting
confidence: 56%
“…Similar findings were reported, also, in the 4 th instar larvae of S. littoralis after treatment with camphor plant oil followed by chlorpyrifos (Fetoh and Asiry, 2013). Many authors (El-Barky et al, 2008;Fahmy and Dahi, 2009;Rashwan, 2013) reported a moderate induction of AchE activity of the same insect after treatment with Spinetoram or emamectin and teflubenzuron (Assar et al, 2016). The activity of AchE in the 4 th instar larvae of the red flour beetle Tribolium castaneum was significantly induced by garlic essential oil (Allium sativum) (El-Gizawy et al, 2019).…”
Section: Discussionsupporting
confidence: 77%